L'Œuvre sans fin. Réception des romans de Monique Saint-Hélier par la critique française (1932-1955) - Dubois, Maud (Histoire des Idées et Critique Littéraire, 2013)
Monique Saint-Hélier became quite successful during the 1930s in particular because of the violent controversy that surrounded her second novel, Bois-Mort. How is it that Saint-Hélier's work provoked such passionate criticism, but encountered nothing but disinterest after the war? Studying unpublished sources as well as a vast corpus of book reviews, the author explores by this quite particular literary path, as well as the variations in how a work is received over time.